Histopathological effects of water soluble–fraction of crude oil on liver tissue of fingerling beluga , Huso huso Linnaeus, 1754 - Khabakhsh, E.; Jamili, Sh.; Motalebi, A.; Mashinchian moradi, A.; Nasrolahzade Saravi, H. (2014)
In this study the LC50 96h values of water-soluble fractions (WSF) of the Caspian Sea – exploited crude oil were determined in beluga, Huso huso fingerlings. The fingerlings averaged 2.42 ± 0.11 g in weight were exposed to WSF crude oil at concentrations 24.75, 27, 29.25, 31.5, 33.75, 36, 38.25 ppm. The treatments were performed in three replicates and all changes in the specimens were determined for each concentration. Water quality parameters of the seawater were tested and recorded. The LC50 96h value was found to be 34.87 ppm. In the other step, the fingerling beluga was exposed to three sub-lethal concentrations (13.93, 20.92, 27.90 ppm) of WSF of the Caspian crude oil representing 40, 60 and 80% of LC50 96h respectively, and control without crude oil. All treatments and control were conducted in triplicate. Three specimens of each treatment were sampled for histological studies every day. Results revealed that the fish liver tissue of all the treatments showed histological changes, in comparison to the control after 2 days. Even if the changes in the treatment exposed to 27.90 ppm (80% LC50 96h) WSF occurred in 24h after exposure. Histopathological findings in liver included cloudy swelling, pyknotic nuclei, Karyorrhectic nuclei, fatty vacuolation, fatty degeneration, hypertrophy of hepatocyte, necrosis, hypertrophy of bile ducts, cholestasis and bile stagnation, inflammation, fibrosis and cirrosis. These alterations were more conspicuous with increasing the soluble fraction of crude oil concentrations and exposing time. The results are of importance since much attention has been paid to the oil slicks, particulate or sedimentary pollutions, instead of potential toxic effects of water-soluble fractions of oil, which are more available to marine biota. Published